CLASS EXERCISES FOR SOCIOLOGY OF GENDER - Borland, Elizabeth (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The following describes three exercises that I have used teaching sociology of gender. The first is from the first day of class, the second from the last day of class, and the third from a unit on gender violence. I used these exercises while teaching a class with 65 students at the University of Arizona, but they could be used with any size class. The attached materials are handouts that go with the assignments.